2017
DOI: 10.3892/br.2017.876
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA CCAT1 is overexpressed in oral squamous cell carcinomas and predicts poor prognosis

Abstract: Abstract. Oral squamous cell carcinoma (SCC) is the most common malignant tumor in India with 5-year survival rates totaling <50%. Recently, dysregulation of non-coding RNA was reported as a potential hallmark of carcinogenesis. Colon Cancer Associated Transcript 1 (CCAT1), an lncRNA located in chromosome 8q24, close to the c-Myc gene, has been reported to be overexpressed in many human cancers. In the present study, the authors analyzed the expression of CCAT1, c-Myc and the miRNAs miR155-5p, let7b-5p, miR490… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 31 publications
0
38
0
Order By: Relevance
“…In a group of 62 OSCCs, underexpression of PTENp1 was observed in all the lesions from buccal mucosa or gingiva, in 71% of lesions from the lip and in 77% of lesions from the tongue (Gao et al, 2017). Arunkumar, Murugan et al (2017) reported that overexpression of CCAT1 was found in only 27% of 60 OSCC cases, but the majority of the CCAT1-overexpressing samples (62.5%) were tumours from buccal mucosa. Moreover, in the presence of tobacco smoking or tobacco chewing/smoking a high expression of CCAT1 was observed.…”
Section: Anatomical Subsite As a Potential Confounding Factormentioning
confidence: 99%
See 2 more Smart Citations
“…In a group of 62 OSCCs, underexpression of PTENp1 was observed in all the lesions from buccal mucosa or gingiva, in 71% of lesions from the lip and in 77% of lesions from the tongue (Gao et al, 2017). Arunkumar, Murugan et al (2017) reported that overexpression of CCAT1 was found in only 27% of 60 OSCC cases, but the majority of the CCAT1-overexpressing samples (62.5%) were tumours from buccal mucosa. Moreover, in the presence of tobacco smoking or tobacco chewing/smoking a high expression of CCAT1 was observed.…”
Section: Anatomical Subsite As a Potential Confounding Factormentioning
confidence: 99%
“…The lncRNA colon cancer-associated transcripts CCAT1 and CCAT2 have been reported to behave differently in OSCC; CCAT1 was found to be overexpressed in only 27% of OSCC (Arunkumar, Murugan, et al, 2017), while CCAT2 was found to be significantly overexpressed (Ma et al, 2017;Zhou et al, 2016).…”
Section: Yu Et Al Validated the Overexpression In Tscc Of Linc00152mentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the variant rs7763881 in HULC has been found to be associated with a decreased risk of HCC in persistent carriers of HBV . Recently, CCAT1 has been demonstrated to be upregulated and shown to predict poor prognosis in oral squamous cell carcinomas (Arunkumar et al 2017).…”
Section: Lncrnas In Human Cancersmentioning
confidence: 99%
“…A few lncRNAs including MEG3, PTENP-AS1, PANDAR and GAS5 functions as tumor suppressors and several other lncRNAs are well established to function as oncogenes in various cancers [12]. HOTAIR, linc-ROR, H19, CCAT1, ZEB1-AS1, NEAT1, MALAT1, UCA1 and CDKN2B-AS1 are well documented to be upregulated in oral cancer [12,14,15]. LncRNAs function by acting as signals, decoys, guides, and scaffolds and as a repressor or activator of gene transcription and translation.…”
Section: Introductionmentioning
confidence: 99%